(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Drugs bearing indole alkaloids are known to produce important pharmacological effects. Kopsia fruticosa (KF), member of thee Genus Kopsia containing four indole alkaloids possesses central nervous system (CNS) pharmacological effects. This study was conducted to explore the CNS effects of KF in rodents. Materials and Methods: The propylene glycolic solution (KF1) and aqueous solution (KF2) were prepared from the dried extract of the leaves of KF. Evaluation of hexobarbitone induced sleeping time in mice, analgesic effect by Tail flick response on thermal stimulus in rats, locomotor activity by Spontaneous motor activity and rotarod method in rats, sedative ataxic score by inclined plane method in mice and behavioural activity by Gross behavioural effects, Conditional Avoidance response, and cataleptic effects in rats were performed at 2, 4, 8,16 mg/kg of body weight respectively. Results: KF1 reduced the spontaneous locomotor activity and exploratory behaviour in mice (p<0.001-0.01) more than KF2. KF1 in all doses potentiated the hypnotic dose (p<0.001) of hexobarbitone and sub-hypnotic dose (upto 80% potentiation) of hexabarbitone as compared to only 40% potentiation by KF2. Anti-nociception effect was found to be absent at all doses. KF1 possesses moderate sedative ataxic effect (p<0.001) and KF2 at 8mg/kg b.w. revealed mild effect (p<0.05) when compared to pentobarbitone. KF1 induced a moderate degree of catalepsy and potentiated cataleptic and sub-cataleptic doses of haloperidol at all doses (p<0.001). Conclusion: The present study has revealed that the propylene glycolic extract of the leaves Kopsia fruticosa possesses profound action on the CNS thereby paving the way to further research.